2008
DOI: 10.1038/ijir.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

Early endothelial dysfunction as a marker of vasculogenic erectile dysfunction in young habitual cannabis users

Abstract: Aim of the study was to evaluate whether endothelial dysfunction is a marker of erectile dysfunction (ED) in recreational drug abuse. Sixty-four non-consecutive men complaining of ED from at least 3 months were included. All patients underwent detailed history about recreational drug abuse and were then submitted to dynamic penile duplex ultrasound (PDU). According to pharmaco-stimulated peak systolic velocity (PSV) cutoff at 35 cm s À1 , patients were divided into two groups: organic (O; n ¼ 30) and non-organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 40 publications
1
44
1
2
Order By: Relevance
“…Similarly, it was also showed in another recent study that chronic cannabis consumption can cause vascular ED in young habitual cannabis users through its effect on endothelial function [126]. However, no link between frequency of cannabis use and trouble keeping an erection was reported in a study where 4350 men were screened for the use of cannabis and its sexual effects [127].…”
Section: Effect On Libido and Sexual Functionmentioning
confidence: 87%
“…Similarly, it was also showed in another recent study that chronic cannabis consumption can cause vascular ED in young habitual cannabis users through its effect on endothelial function [126]. However, no link between frequency of cannabis use and trouble keeping an erection was reported in a study where 4350 men were screened for the use of cannabis and its sexual effects [127].…”
Section: Effect On Libido and Sexual Functionmentioning
confidence: 87%
“…Cohen (1982) compared the prevalence of ED in daily cannabis users and a male control group and reported an ED rate in the cannabis users more than double that in the controls. Similarly, another study showed that chronic cannabis consumption can cause vascular ED via its effect on endothelial function (Aversa et al, 2008). Abel (1981) concluded in a review of cannabis and sexuality that a small amount of cannabis can enhance sexual pleasure, but larger quantities can diminish sexual desire.…”
Section: Discussionmentioning
confidence: 98%
“…PE is described to be linked with high alcohol consumption and former smoking [8]. ED is reported to be linked not only with alcohol and tobacco use [22] but also with cannabis [23]. The role of other illegal drugs is complex because they are supposed to increase not only ED but also ejaculation latency [24].…”
mentioning
confidence: 98%